The association between parental supply of alcohol and supply from other sources to young people: a prospective cohort. (24th March 2020) - Boland, Veronica C.; Clare, Philip J.; Yuen, Wing See; Peacock, Amy; Aiken, Alexandra; Wadolowski, Monika; Hutchinson, Delyse; Najman, Jackob; Slade, Tim; Bruno, Raimondo; McBride, Nyanda; Degenhardt, Louisa; et al.
Abstract: Aims: Despite legal age limits set for alcohol consumption, parents are one of the main suppliers of alcohol to underage minors. Although supply from non‐parental sources has been found to be associated with greater risk of harm compared with parental supply, the association between parental supply and supply from other sources is unclear. This study investigated the associations between parental supply of sips and whole serves of alcohol on subsequent other supply, conditional on current supply from non‐parental sources. Methods: Data from the Australian Parental Supply of Alcohol Longitudinal Study cohort of adolescents was used. A cohort of 1927 Australian children recruited in grade 7 (mean age 12.9 years) was surveyed annually from 2010 to 2016 (94%, n  = 1821 included for analyses). The primary outcome was alcohol exposure from other sources ('other supply'), including alcohol supply from other adults, friends, siblings, or self‐supply, compared with adolescents reporting no supply from these sources. Analyses were conducted using random intercept logistic regression (to account for within‐respondent correlation). Results: Parental supply of alcohol alone was associated with increased odds of receiving alcohol from other non‐parental sources in subsequent years (OR: 1.99; 95% CI: 1.65–2.39) after adjusting for confounders. Increased odds of subsequent other supply were associated with current parental supply of sips (OR: 1.92; 95% CI: 1.56–2.36) and whole drinks (OR: 2.76; 95% CI: 1.85–4.11). Conclusions: Parental supply of alcohol appears to increase the risk of subsequent supply of alcohol from other sources in certain contexts.